Penerapan Teknik Mutual Storytelling dalam Mengatasi Sibling Rivalry Pada Klien “A” di TPA Masjid Nurul Falah Pakjo Palembang - Sri Meithiya, Annisa; Noviza, Neni; Janare Putra, Bela (Social Science and Contemporary Issues Journal, 2024)
This research is entitled "Application of Mutual Storytelling Techniques to Overcome Sibling Rivalry in Client "A" at the Nurul Falah Pakjo Mosque Landfill Palembang". This research aims to find out how the sibling rivalry condition experienced by client "A" is described, to find out how the mutual storytelling technique is applied in overcoming sibling rivalry in client "A" at the Nurul Falah Pakjo Mosque Landfill Palembang. This study uses a qualitative approach with a case study method. The subject of the study is client "A". The data collection techniques used are observation, interviews, and documentation. Meanwhile, the data analysis techniques used are pattern matching, explanatory and time series analysis. The results of this study are that there is a description of the condition experienced by client "A" seen based on his characteristics such as aggressive behavior (resentment, anger, hatred), spirit of competition or not like to give in to siblings, and the appearance of feelings of envy or jealousy.